Evaluation of adhesion properties in bitumen-aggregate systems for winter surfacing seals using the bitumen bond strength test - Twagirimana, Emmanuel (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2014.